MANAGING EDUCATIONAL INSTITUTIONS: LEGAL REQUIREMENTS IN THE CONTEXT OF LEADERSHIP - Kriviņš, Anatolijs; Jankovska, Līvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The research analyses the problem of recruiting managers of educational institutions, paying special attention to the leadership aspect. The topicality of the article is related to the fact that in the Republic of Latvia positions of this level require the holding of job competitions, which is why the mentioned competitions are held regularly. The research novelty: interdisciplinary research analyzing scientific articles, Latvia's education policy documents and normative legal acts, announcements of job competitions in the official publication of the Republic of Latvia "Latvijas Vestnesis" - using comparison, deduction and induction methods were carried out. A summative content analysis was performed. The research aim is to find out to what extent the leadership aspects are taken into account in job contests (for the management of education institutions - rector of a higher education institution or a director of college). 70 advertisements (in competitions for the position of higher education institution rector) for the period from 2004 to 2023, as well as 18 advertisements (in competitions for the position of college director) for the period from 2008 to 2022 were analyzed. As a result of the analysis, it was concluded that, despite the content of regulatory legal acts, the demand for leadership positions as a tender announcer is extremely rare. The authors of the article propose to normatively strengthen the obligation of the organizer of the job competition to include the leadership requirement as mandatory, as well as to develop a system of leadership tests at the national level.